PERANCANGAN MEDIA PERMAINAN PENJUMLAHAN “TIC TAC TIKA” UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN SISWA SEKOLAH DASAR - Wahyu Asna Fauziatul Maghfiroh; Elok Fariha Sari (Joyful Learning Journal, 2025)
Low addition skills and the perception that mathematics is a difficult and boring subject because it is synonymous with numbers indicate the need for innovative learning media that is interesting and suited to the characteristics of elementary school students. This study aims to design a Tic Tac Tika addition game to improve the addition skills of second-grade elementary school students. This media adopts the concept of tic tac toe with the addition of sums up to 20. This study uses R&D research with an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development approach. Data collection techniques were carried out through observation, interviews, distribution of questionnaires, documentation, etc. The results showed that the Tic Tac Tika addition game was very suitable for use as a mathematics learning medium based on the results of subject matter expert validation of 91% and media expert validation of 91%. In addition, the response from teachers was also very positive, stating that this media was able to create mathematics learning that was fun, practical, and in line with learning outcomes. Thus, the Tic Tac Tika addition game media is feasible and has great potential to help students improve their addition skills in a fun way.